Quorum sensing N-Acyl homoserine lactones are a new class of anti-schistosomal. - Helen Whiteland; Alessandra Crusco; Lisa W Bloemberg; Jamie Tibble-Howlings; Josephine Forde-Thomas; Avril Coghlan; Patrick J Murphy; Karl F Hoffmann (Public Library of Science (PLoS), 2020)
Background Schistosomiasis is a prevalent neglected tropical disease that affects approximately 300 million people worldwide. Its treatment is through a single class chemotherapy, praziquantel. Concerns surrounding the emergence of praziquantel insensitivity have led to a need for developing novel anthelmintics. Methodology/principle findings Through evaluating and screening fourteen compounds (initially developed for anti-cancer and anti-viral projects) against Schistosoma mansoni, one of three species responsible for most cases of human schistosomiasis, a racemic N-acyl homoserine (1) demonstrated good efficacy against all intra mammalian lifecycle stages including schistosomula (EC50 = 4.7 μM), juvenile worms (EC50 = 4.3 μM) and adult worms (EC50 = 8.3 μM). To begin exploring structural activity relationships, a further 8 analogues of this compound were generated, including individual (R)- and (S)- enantiomers. Upon anti-schistosomal screening of these analogues, the (R)- enantiomer retained activity, whereas the (S)- lost activity. Furthermore, modification of the lactone ring to a thiolactone ring (3) improved potency against schistosomula (EC50 = 2.1 μM), juvenile worms (EC50 = 0.5 μM) and adult worms (EC50 = 4.8 μM). As the effective racemic parent compound is structurally similar to quorum sensing signaling peptides used by bacteria, further evaluation of its effect (along with its stereoisomers and the thiolactone analogues) against Gram+ (Staphylococcus aureus) and Gram- (Escherichia coli) species was conducted. While some activity was observed against both Gram+ and Gram- bacteria species for the racemic compound 1 (MIC 125 mg/L), the (R) stereoisomer had better activity (125 mg/L) than the (S) (>125mg/L). However, the greatest antimicrobial activity (MIC 31.25 mg/L against S. aureus) was observed for the thiolactone containing analogue (3). Conclusion/significance To the best of our knowledge, this is the first demonstration that N-Acyl homoserines exhibit anthelmintic activities. Furthermore, their additional action on Gram+ bacteria opens a new avenue for exploring these molecules more broadly as part of future anti-infective initiatives.